Development of Local Supply Chain : A Critical Link for Concentrated Solar Power in India - World Bank (Washington, DC, 2014)
Amid the success of Solar Photovoltaic (PV) projects in India, Concentrated Solar Power (CSP) technology also provides a compelling case for support by the government as among solar technologies; CSP is the only techno-economically viable option at present that provides a storage option for dispatchable and dependable solar energy. Furthermore, the conversion of solar to steam is a relatively high-efficiency process versus the conversion efficiency of PV. This process can effectively supplement fossil fuels and renewable fuel, such as biomass, and thus contribute to the overall energy security of the country. The specific objective of the study is to assess the potential of India's industries to set up a manufacturing base to produce CSP technology components and equipment. The study assesses competitive positioning and the potential of Indian companies in the manufacturing of important CSP components. Various analysis models were prepared for the analysis, and the details have been explained in the elaborated version of the report. The report also proposes an action plan to help develop this potential and evaluate the resulting economic benefits. This report includes the following activities: i) assessment of the competitive position of local industries to support the development of CSP technologies in India; ii) evaluation of short, medium, and long-term economic benefits of creation of a local manufacturing base; and iii) action plan to stimulate local manufacturing of CSP technology components and equipment. This document is a summary of the larger report. The data analysis and messages presented in the report are based on very limited information presently available in the Indian market. Therefore, it is recommended that the trends and ideas to be given more attention than the data itself.